Mechanical Properties of Unsaturated Granular Materials - Katebi-Zaki, Arash (My University, 2004)
The mechanistic design of flexible pavement systems requires the specification of the mechanical properties of unbound granular base/subbase material. The influence of the degree of saturation, low confining pressure, and suction (measured through an SWCC test) on the monotonic and cyclic behavior of granular base/subbase was investigated to obtain a better understanding of granular base behavior corresponding to condition encountered in situ.
In order to achieve this understanding, a series of quick-undrained (UU) monotonic and cyclic triaxial tests were conducted on sand specimens (Material 1 and Material 2) at ambient temperature, with the degree of saturation ranging from 24% to 66%, and confining pressures from 4 kPa to 64 kPa. Additional tests were conducted under UU conditions to determine the effects of freeze-thaw on permanent deformation (plastic strain) and the memory of base material.
The results showed that shear strength and modulus of elasticity increase with increasing confining pressure, and decrease with increasing water content (degree of saturation), as expected. The stress-strain response of the specimens was generally ductile with higher confining pressure and degree of saturation causing greater ductility. The cyclic test results showed that there was a monotonic relationship between accumulated plastic strain and confining pressure, given that ratio of peak shear stress to confining presseure is constant. The research also showed that there is an almost linear relationship between increase plastic strain and moisture content after cyclic tests or freeze-thaw. Overall it was found that the effect of saturation and change in suction on shear strength and modulus of elasticity is not as significant as the effect of confining pressure. However, it was found that the effects of saturation, suction, and confining pressure were almost equally important when it comes to plastic strain development during cyclic tests or freeze-thaw loading.
Keywords: Civil Engineering; Civil Engineering